Parental Experience on Female Circumcision in East Coast of Malaysia - Suhaimi, Nailil Hanani; Zakaria, Rosnani; Muhamad, Rosediani; Mohd Zulkifli, Maryam (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Female circumcision (FC) is a deep-rooted tradition in Malaysia, influenced by religious, cultural, and health beliefs. However, it has drawn criticism for its similarities to Female Genital Mutilation (FGM) in Africa, particularly during the 2018 Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) by the United Nations Human Rights (UNHR). Amidst this backdrop, this study aimed to investigate parents’ perspectives and experiences concerning female circumcision, as well as the factors driving its persistence. MATERIALS AND METHODS: This qualitative study used phenomenological approach and 20 in-depth interviews were conducted using a semi-structured questionnaire until data saturation were reached. We employed convenience and snowball sampling methods. The interviews were recorded, transcribed, and analyzed using NVivo 12 software. We used thematic analysis to identify key themes in the data. RESULTS: Three themes emerged from the interviews: (1) FC is a ‘fitrah’, (2) maintaining good health is the main influence; and (3) FC causing no harm. The main influences on this practice are religious, cultural, and health factors. Parents described the procedure as simple and harmless for the baby and themselves, both physically and emotionally. CONCLUSIONS: This research shown that FC in Malaysia is not solely religious but deeply embedded in culture. The blend of cultural and religious aspects makes it a crucial practice for some.